Impact of HLA-B*81-associated mutations in HIV-1 Gag on viral replication capacity. - Wright, J; Naidoo, V; Brumme, Z; Prince, J; Claiborne, D; Goulder, P; Brockman, M; Hunter, E; Ndung'u, T (2012)
HIV-1 attenuation resulting from immune escape mutations selected in Gag may contribute to slower disease progression in HIV-1-infected individuals expressing certain HLA class I alleles. We previously showed that the protective allele HLA-B*81 and the HLA-B*81-selected Gag T186S mutation are strongly associated with a lower viral replication capacity of recombinant viruses encoding Gag-protease derived from individuals chronically infected with HIV-1 subtype C. In the present study, we directly tested the effect of this mutation on viral replication capacity. In addition, we investigated potential compensatory effects of various polymorphisms, including other HLA-B*81-associated mutations that significantly covary with the T186S mutation. Mutations were introduced into a reference subtype B backbone and into patient-derived subtype C sequences in subtype B and C backbones by site-directed mutagenesis. The exponential-phase growth of mutant and wild-type viruses was assayed by flow cytometry of a green fluorescent protein reporter T cell line or by measurement of HIV-1 reverse transcriptase activity in culture supernatants. Engineering of the T186S mutation alone into all patient-derived subtype C sequences failed to yield replication-competent viruses, while in the subtype B sequence, the T186S mutation resulted in impaired replication capacity. Only the T186S mutation in combination with the T190I mutation yielded replication-competent viruses for all virus backbones tested; however, these constructs replicated slower than the wild type, suggesting that only partial compensation is mediated by the T190I mutation. Constructs encoding the T186S mutation in combination with other putative compensatory mutations were attenuated or defective. These results suggest that the T186S mutation is deleterious to HIV-1 subtype C replication and likely requires complex compensatory pathways, which may contribute to the clinical benefit associated with HLA-B*81.